Automating Business Process Modeling: An LLM-Based Approach with Situation-Based Modeling Notation - Souza, Gean Paulo O.; Oliveira, Hilário Tomaz A. de; Costa, Mateus Barcellos (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2026)
Research Context: Although business process modeling is beneficial for clarifying organizational processes, it remains a task with little automation and requires significant human effort. Scientific and/or Practical Problem: To reduce this effort, research has advanced toward automating the task, mainly focusing on extracting imperative models from textual descriptions. However, imperative models may lead to a single solution that does not necessarily represent the best fit. Proposed Solution and/or Analysis: The declarative Situation-Based Modeling Notation (SBMN) allows modelers to generate multiple modeling structure alternatives, enabling them to choose the one that best fits the context. This work investigates the use of Large Language Models (LLMs) to identify core business process entities and constraints represented in SBMN from textual descriptions. Related IS Theory: This research is grounded in the Task-Technology Fit (TTF) theory, applied to evaluate the adequacy of LLMs in supporting business process analysts during modeling activities. Research Method: A dataset of 133 textual descriptions paired with SBMN models was employed. Each description was processed by three medium-scale LLMs and three extra-large LLMs using zero-shot prompts to identify domain situations and Active Flow Objects. The outputs were semantically compared with the corresponding SBMN models to measure their similarity. Summary of Results: Large-scale LLMs (e.g., Claude Sonnet and Qwen3-80B) were able to identify flow objects and situations in SBMN with relevant accuracy, demonstrating the feasibility of their use to support the modeling task. Contributions and Impact to IS area: This research provides: (i) empirical evidence highlighting the strengths and limitations of current LLMs in the process modeling domain; (ii) a dataset containing aligned pairs of textual descriptions and SBMN models; and (iii) a semantic–structural similarity metric enabling the quantitative evaluation of SBMN component extraction accuracy from text.